A Longitudinal Ambulatory Quality Improvement Curriculum That Aligns Resident Education With Patient Outcomes: A 3-Year Experience. (May 2020) - Parekh, Natasha; Lebduska, Elena; Hoffman, Erika; Kohli, Amar; Demoise, David; Jeong, Kwonho; Rothenberger, Scott; Fischer, Gary S.; Spagnoletti, Carla; Hariharan, Jaishree
Quality improvement (QI) plays a vital role in practice management, patient care, and reimbursement. The authors implemented a 3-year longitudinal curriculum that combined QI didactics, intervention development, and implementation at university-based, community-based, and Veterans Administration–based practices. Highlights included Plan-Do-Study-Act cycle format, team-based collaboration to brainstorm interventions, interdisciplinary QI council to select and plan interventions, system-wide intervention implementation across entire clinic populations with outcome monitoring, and intervention modifications based on challenges. A pre–post survey assessed residents' confidence in QI skills and interdisciplinary team participation, while quarterly quality data assessed patient outcomes. All 150 internal medicine residents participated. Confidence in QI and interdisciplinary team participation improved significantly ( P < .001). Patient outcomes improved for 6 of 9 targeted projects and were sustained at 1 year. This curriculum is a systems-based innovation designed to improve patient care and encourage interdisciplinary teamwork and can be adopted by residencies seeking to improve engagement in QI.